1985
DOI: 10.1038/315226a0
|View full text |Cite|
|
Sign up to set email alerts
|

X-linkage of steroid sulphatase in the mouse is evidence for a functional Y-linked allele

Abstract: In the human there is an X-linked gene affecting steroid sulphatase (STS) activity which, when deficient, is associated with X-linked congenital ichthyosis. The gene (STS) is located on the distal tip of the short arm and is only partially inactivated when it is on the inactive X-chromosome. In the mouse, the genetics of STS are not clear; the results of one study using XX:X0 oocyte comparisons indicated X-linkage, but three other studies using STS variants have produced segregation data compatible with autoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(42 citation statements)
references
References 31 publications
1
41
0
Order By: Relevance
“…EVANS et al (10) demonstrated that male determining genes, translocated to the tip of the long arm of the Y chromosome, were transferred to the X chromosome by means of an obligate crossover resulting in sex reversal in the progeny. KE1TGES et al (21) have likewise demonstrated that a mouse steroid sulphatase variant appears to be present distal to the site for an obligate crossover between the sex chromosomes. In contrast, all other genetic and structural markers on the X chromosome including distal markers in the long arm are X-linked showing that the obligate crossover is close to the telomere of the X and Y chromosomes (10).…”
Section: Chromosome Pairing and Crossing Overmentioning
confidence: 95%
“…EVANS et al (10) demonstrated that male determining genes, translocated to the tip of the long arm of the Y chromosome, were transferred to the X chromosome by means of an obligate crossover resulting in sex reversal in the progeny. KE1TGES et al (21) have likewise demonstrated that a mouse steroid sulphatase variant appears to be present distal to the site for an obligate crossover between the sex chromosomes. In contrast, all other genetic and structural markers on the X chromosome including distal markers in the long arm are X-linked showing that the obligate crossover is close to the telomere of the X and Y chromosomes (10).…”
Section: Chromosome Pairing and Crossing Overmentioning
confidence: 95%
“…ANT3 mapped separately on another wallaby autosome, so it may represent a region added independently to the eutherian PAR or a region that has been rearranged in marsupials [61]. The mouse sex chromosomes have a 2 Mb PAR region, but contain only one active gene, Sts [62,63]. One other gene, Fxy, spans the pseudoautosomal boundary on the mouse X and has a truncated partner at the boundary of the Y PAR [64,65].…”
Section: Origin Of Human Par1 and Par2mentioning
confidence: 99%
“…Sts (steroid sulfatase; U37545) is the only gene that has been known to be located in the mouse PAR (21,22), whereas it has not mapped on the reference genome sequence (Build 37). We confirmed that the BAC clone contained the Sts gene.…”
mentioning
confidence: 99%